2010
DOI: 10.4061/2010/124264
|View full text |Cite
|
Sign up to set email alerts
|

Profile of Hashimoto's Thyroiditis in Sri Lankans: Is There an Increased Risk of Ancillary Pathologies in Hashimoto's Thyroiditis?

Abstract: Hashimoto's thyroiditis has been reported to be associated with many neoplastic and nonneoplastic thyroid pathologies. This retrospective study aims to determine the demographic profile of Hashimoto's thyroiditis in Sri Lankans, document ancillary pathologies in Hashimoto's thyroiditis, and determine whether there is an increased risk of occurrence of malignancies, benign neoplasms, and nonneoplastic benign lesions in Hashimoto's thyroiditis by comparing with thyroids showing multinodular goiters, follicular a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 20 publications
(34 reference statements)
3
17
0
Order By: Relevance
“…The prevalence of coexisting of HT and DTC in thyroidectomy specimen ranges between 9.4 to 36%. [7][8][9] In our study, 47.4% of patients with DTC had associated HT. The mechanism behind this association is poorly understood.…”
Section: Discussionsupporting
confidence: 44%
“…The prevalence of coexisting of HT and DTC in thyroidectomy specimen ranges between 9.4 to 36%. [7][8][9] In our study, 47.4% of patients with DTC had associated HT. The mechanism behind this association is poorly understood.…”
Section: Discussionsupporting
confidence: 44%
“…The sensitivity analyses revealed that no study had a significant influence on the overall estimates. The pooled ORs for HT varied from 2.04 (when excluding Siriweera et al [ 18 ]) to 2.24 (when excluding Matesa-Anic et al [ 23 ]). The shape of the funnel plot of studies assessing the association between HT and PTC risk seemed to be symmetrical, indicating the absence of publication bias (Figure 5 ).…”
Section: Resultsmentioning
confidence: 99%
“…Hashimoto’s thyroiditis (HT) is a frequent autoimmune thyroid disease, affecting approximately 5% of the general population, especially women [ 1 ]. HT is characterized by intrathyroidal monocyte infiltration along with rising serum autoantibodies, such as anti-thyroglobulin antibody (anti-Tg) and anti-thyroid peroxidase antibody (anti-TPO), and is the leading cause of hypothyroidism worldwide [ 2 ].…”
Section: Introductionmentioning
confidence: 99%